Analysis of Heavy Metals Distribution in the River Town of Hamasaki's Rod Padangsidimpuan - Fatma Suryani Harahap; Laila Tussifah Lubis (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2018)
Systems of waste management in Padangsidimpuan City is an open dumping system. The location of the Padangsidimpuan City landfill is carried out at the Batu Bola TPA located in Batu Bola Village which is 120 meters from the Batang Ayumi river flow. Continuous landfill in the landfill produces pollutants in the form of leachate. Leachate contains organic materials and heavy metals. Heavy metals that are often found in leachate water are Iron (Fe) cadmium (Cd) and Zinc (Zn). This research aims to know the quality of the water of the Batang Ayumi river in terms of the content of heavy metals Cd, Zn, and Fe. This research uses descriptive exploratory method by conducting a survey first. The determination of the sampling location using purposive sampling method at four stations specified. River water sampling is carried out twice, before and after rain. This research uses an Atomic Absorption Spectrophotometer tool. The data obtained were analyzed by comparing research data with water quality standards based on PP. No. 82 of 2001 to look at the conditions of the heavy metal pollution of Cd, Zn and Fe. The results of this study showed that the average concentration of the metal content Cd, Zn and Fe werw below the specified quality threshold, namely the concentration of metal Cd of all stations is 0.0009 mg/l, a concentration of metal Fe is 0.03 mg/l, and concentration of Zn metal is 0.0002 mg/l.